2018
DOI: 10.1002/ejoc.201801250
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Synthesis of Oxazolidine‐2,4‐diones and 3,3‐Disubstituted Oxindoles via ICl‐Induced Cyclization

Abstract: A metal‐free method for the construction of oxazolidine‐2,4‐diones and oxindoles was discussed. Using iodine monochloride (ICl) as both the reaction promoter and iodide source, the iodolactonization of N‐Boc acrylamides proceeded readily and provided the corresponding iodo oxazolidine‐2,4‐diones and oxazolidin‐2‐ones in good isolated yields. The obtained oxazolidine‐2,4‐diones can be used as key intermediates in the synthesis of toloxatone. When N‐alkyl‐N‐arylacrylamide derivatives were subjected to the same r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 103 publications
0
13
0
Order By: Relevance
“…In a different approach in 2018, Liu and colleagues reported the metal‐free route to access oxazolidine‐2,4‐diones 59 and oxindoles 61 in which iodine monochloride acts as reaction stimulant and source of iodine in the transformation (Scheme 14). [23] In the instance of accessing oxazolidine‐2,4‐diones 59 , acrylamides 58 were reacted in the presence of equimolar quantities of iodine monochloride and sodium hydrogen carbonate under ambient conditions – the desired iodocyclized products 59 (21 examples, 63–92 %) could be isolated with an added advantage, no need for chromatographic purification, a simple extraction after quenching with sodium thiosulfate sufficed. The application of such products accessed in Scheme 14a through post‐structural modifications include oxazolidinedione ring opening, or alternatively replacing the terminal iodine atom to a hydroxyl moiety.…”
Section: Cyclization Reactions/carbonyl Olefin Metathesis Reactions Mediated By Iodine Monochloridementioning
confidence: 99%
“…In a different approach in 2018, Liu and colleagues reported the metal‐free route to access oxazolidine‐2,4‐diones 59 and oxindoles 61 in which iodine monochloride acts as reaction stimulant and source of iodine in the transformation (Scheme 14). [23] In the instance of accessing oxazolidine‐2,4‐diones 59 , acrylamides 58 were reacted in the presence of equimolar quantities of iodine monochloride and sodium hydrogen carbonate under ambient conditions – the desired iodocyclized products 59 (21 examples, 63–92 %) could be isolated with an added advantage, no need for chromatographic purification, a simple extraction after quenching with sodium thiosulfate sufficed. The application of such products accessed in Scheme 14a through post‐structural modifications include oxazolidinedione ring opening, or alternatively replacing the terminal iodine atom to a hydroxyl moiety.…”
Section: Cyclization Reactions/carbonyl Olefin Metathesis Reactions Mediated By Iodine Monochloridementioning
confidence: 99%
“…The Liu group recently reported the protection group dependent selective iodo-cyclizations of N -protected N -aryl-acrylamides using ICl in the presence of NaHCO 3 [ 110 ]. Oxazolidine-2,4-diones 114 were obtained by exo-type iodolactonizations of N -Boc N -arylacrylamides 113 , while oxindoles 114′ were prepared by exo-type iodocarbocyclizations of N -alkyl N -arylacrylamides 113′ ( Figure 53 ).…”
Section: Substrate-switchable Cyclizationsmentioning
confidence: 99%
“…In addition, Cao et al reported a metal-free example of this reaction, while Zhang et al have generated aminooxylated oxindoles using a similar strategy . Alternatively, N -Boc acrylamides have been found to undergo cyclization with the alkene generating a variety of 5,5′-disubstituted oxazolidine-2,4-diones with the introduction of C–F, C–N, and C–I bonds (Figure B). We now report that metal-free hypervalent iodine mediated oxidative cyclization of N -Boc-acrylamides provides an efficient route to 5,5-disubstituted oxazolidine-2,4-diones with the formation of a C–O bond (Figure C) . Furthermore, the reaction takes place with an array of N-substituents, is diastereospecific with N -Boc-2,3-dimethylacrylamides, and occurs with phenyl migration in the case of an N -Boc-2-phenylacrylamide.…”
mentioning
confidence: 99%
“…Presumably the (diacetoxyiodo)­benzene coordinates with the alkene via intermediate A (Scheme ) that can undergo cyclization with loss of isobutylene to generate an intermediate such as B . This is consistent with the stereochemical course reported for the ICl-induced iodo-cyclization of similar N -Boc-acrylamide substrates . This could be followed by S N 2-like substitution of PhI­(OAc) with stereocenter inversion resulting in 6b .…”
mentioning
confidence: 99%
See 1 more Smart Citation